2006
DOI: 10.1212/01.wnl.0000234129.97727.4d
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset metachromatic leukodystrophy

Abstract: The characteristic clinical differences between homozygous P426L and compound heterozygous I179S patients establish a distinct genotype-phenotype correlation in late-onset metachromatic leukodystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(56 citation statements)
references
References 27 publications
3
53
0
Order By: Relevance
“…For many lysosomal storage disorders, residual enzymatic activity and phenotype have been linked to patients' genotype (Kroos, et al, 2008;Schaefer, et al, 2005;Scott, et al, 1995). Our group recently confirmed the information on genotype-phenotype correlation for Metachromatic Leukodystrophy, already described for common mutations (Gieselmann, 2005;Polten, et al, 1991;Rauschka, et al, 2006), and expanded it to rare alterations. Moreover, we suggested that a classification based on genotype and residual enzymatic activity of the mutant alleles, analyzed by means of expression studies, may be more reliable than the one based exclusively on age at onset, allowing MLD patients to be classified in genotype-based subclasses according to the combination of 0 and R mutations they carry on their alleles (Biffi, et al, 2008).…”
Section: Introductionsupporting
confidence: 67%
“…For many lysosomal storage disorders, residual enzymatic activity and phenotype have been linked to patients' genotype (Kroos, et al, 2008;Schaefer, et al, 2005;Scott, et al, 1995). Our group recently confirmed the information on genotype-phenotype correlation for Metachromatic Leukodystrophy, already described for common mutations (Gieselmann, 2005;Polten, et al, 1991;Rauschka, et al, 2006), and expanded it to rare alterations. Moreover, we suggested that a classification based on genotype and residual enzymatic activity of the mutant alleles, analyzed by means of expression studies, may be more reliable than the one based exclusively on age at onset, allowing MLD patients to be classified in genotype-based subclasses according to the combination of 0 and R mutations they carry on their alleles (Biffi, et al, 2008).…”
Section: Introductionsupporting
confidence: 67%
“…182,183,192 ARSA mutations characterized in more detail have been divided into two groups: (1) "null alleles" such as c.459 ϩ 1gϾa (25% of disease alleles) and c.1204 ϩ 1gϾa that result in complete loss of enzymatic activity and (2) "R alleles" such as p.P426L (25% of disease alleles) and p.I179S (12.5% of disease alleles) that allow the synthesis of ARSA enzyme with residual catalytic activity of up to 5% of normal. 182,193 Based on this classification, genotype-phenotype correlations have been proposed 194 and further corroborated 192,195,196 to predict, in limited fashion, the clinical presentation and natural history (see Table 5). Although the predictive value of this correlation is excellent for patients homozygous for two null alleles, patients with one and two R alleles show considerable phenotypic variability, implicating other genetic and/or environmental factors that contribute to the disease course.…”
Section: Molecular Analysismentioning
confidence: 88%
“…The majority of cases occur in childhood; however, adult-onset forms of the disease can share similarities with MS (Hirose and Bass, 1972;Klemm and Conzelmann, 1989;Kappler et al, 1991;Rauschka et al, 2006;Gieselmann, 2008). The adult-onset form typically manifests as personality change with progressive dementia.…”
Section: Metachromatic Leukodystrophy (Mld)mentioning
confidence: 99%